Transition probabilities of the seven lowest–lying singlet states of the AlN radical. (February 2019) - Xing, Wei; Shi, Deheng; Sun, Jinfeng; Zhu, Zunlue
Highlights: Lifetimes are 10 −6 to 10 −7  s for the e 1 Δ state and the 1st well of the f 1 Δ state. The d 1 Σ + –a 1 Σ +, d 1 Σ + –b 1 Π, e 1 Π–a 1 Σ +, e 1 Π–b 1 Π, and g 1 Σ − –b 1 Π transitions are strong. Emissions from the 1st well of f 1 Δ state to the b 1 Π and c 1 Δ states can be observed. Lifetimes are approximately 10 −6  s for the d 1 Σ + and g 1 Σ − states. Emissions originating from the 2nd well of the f 1 Δ state are very weak. The emissions of the e 1 Π–d 1 Σ + system are very weak. Abstract: In this study, the potential energy curves are calculated for the a 1 Σ +, b 1 Π, c 1 Δ, d 1 Σ +, e 1 Π, f 1 Δ, and g 1 Σ − states of the AlN radical. The transition dipole moments between them are computed. The rotationless radiative lifetimes of the vibrational levels are found to be approximately several µs for the d 1 Σ + and g 1 Σ − states, on the order of several hundred ns for the e 1 Π state, and one-tenth to several µs for the deep well of the f 1 Δ state. These results suggest that the spontaneous emissions originated from these states occur readily. The rotationless radiative lifetimes of the vibrational levels are on the order of 10–100 µs for the c 1 Δ state, 1000 µs for the vdW minimum of the f 1 Δ state, and 10–1000 µs for the b 1 Π state. In addition, the rotationless radiative lifetimes of these states decrease with the increasing vibrational level. This result suggests that the spontaneous emissions generated from these states at lower levels should be difficult to occur. The Einstein coefficients of spontaneous emissions from the d 1 Σ + –a 1 Σ +, d 1 Σ + –b 1 Π, e 1 Π–a 1 Σ +, e 1 Π–b 1 Π, and g 1 Σ − –b 1 Π systems, as well as from the f 1 Δ state to the b 1 Π and c 1 Δ states are large, indicating that the emissions of these systems can be measured readily via spectroscopy. The Einstein coefficients of the e 1 Π–d 1 Σ + transition are very small and the emissions originating from the vdW minimum of the f 1 Δ state are very weak, predicting that these transitions are very difficult to be detected in spectroscopy experiments. Graphical abstract: Image, graphical abstract The transition probabilities of emissions are calculated between the a 1 Σ +, b 1 Π, c 1 Δ, d 1 Σ +, e 1 Π, f 1 Δ, and g 1 Σ − states of the AlN radical. The rotationless radiative lifetimes of the vibrational levels are approximately 10 −6  s for the d 1 Σ + and g 1 Σ − states, and 10 −6 to 10 −7  s for the e 1 Π state and the first well of the f 1 Δ state, predicting that spontaneous emissions originating from them occur readily. The rotationless radiative lifetimes are about 10 −4 to 10 −5  s for the c 1 Δ state, 10 −3 to 10 −4  s for the second well of the f 1 Δ state, and 10 −3 to 10 −5  s for the b 1 Π state. Emissions from the d 1 Σ + –a 1 Σ +, d 1 Σ + –b 1 Π, e 1 Π–a 1 Σ +, e 1 Π–b 1 Π, and g 1 Σ − – b 1 Π systems, as well as those from the first well of the f 1 Δ state to the b 1 Π and c 1 Δ states are strong. Emissions of the e 1 Π–d 1 Σ + system and emissions originating from the second well of the f 1 Δ state are so weak that they are hardly measured through spectroscopy.